Analisis Karakteristik Penyelesaian Masalah Matematika Siswa Berdasarkan Gaya Kognitif di Kelas VIII - Purnama, I Made Chandra Adi; Suparta, I Nengah; Ardana, I Made (Edumatica : Jurnal Pendidikan Matematika, 2021)
This study aims to analyze the students' mathematical problem-solving characteristics based on cognitive style that is field independent, field dependent, reflective, and impulsive. Fourty-five students of VIII grade at PGRI 5 Junior High School were involved. The students were given 4 descriptive math problems. The result showed that the characteristics of independent field cognitive style showed that could understand the problems, determined the right problem planning, careless in solving, and did not re-check the answer. The subject could solve questions faster than the specified time, but the answer was wrong. For the characteristics of field dependent cognitive style, they could understand the problems, determined the right problem planning, careless in solving, and did not re-check the answer. The subject could not solve questions on time, but the answers tended to be correct. For the characteristics of reflective cognitive style, they did not understand the problems, determined the right problem planning, quite careless in solving, and did not re-check the answer. The subject could solve questions faster than the specified time, but the answer was wrong. For the characteristics of impulsive cognitive style, they did not understand the problems, determined the right problem planning, quite careless in solving, and did not re-check the answer. The subject could solve questions on time, but the answers tended to be wrong.